Electrophysiological and Morphological Maturation of Murine Fetal Cardiomyocytes During Electrical Stimulation In Vitro. (January 2015) - Baumgartner, Sven; Halbach, Marcel; Krausgrill, Benjamin; Maass, Martina; Srinivasan, Sureshkumar Perumal; Sahito, Raja Ghazanfar Ali; Peinkofer, Gabriel; Nguemo, Filomain; Müller-Ehmsen, Jochen; Hescheler, Jürgen
The aim of this study was to investigate whether continuous electrical stimulation affects electrophysiological properties and cell morphology of fetal cardiomyocytes (FCMs) in culture. Fetal cardiomyocytes at day 14.5 post coitum were harvested from murine hearts and electrically stimulated for 6 days in culture using a custom-made stimulation chamber. Subsequently, action potentials of FCM were recorded with glass microelectrodes. Immunostainings of α-Actinin, connexin 43, and vinculin were performed. Expression of ion channel subunits Kcnd2, Slc8a1, Cacna1, Kcnh2, and Kcnb1 was analyzed by quantitative reverse-transcriptase polymerase chain reaction. Action potential duration to 50% and 90% repolarization (APD50 and APD90 ) of electrically stimulated FCMs were significantly decreased when compared to nonstimulated control FCM. Alignment of cells was significantly higher in stimulated FCM when compared to control FCM. The expression of connexin 43 was significantly increased in stimulated FCM when compared to control FCM. The ratio between cell length and cell width of the stimulated FCM was significantly higher than in control FCM. Kcnh2 and Kcnd2 were upregulated in stimulated FCM when compared to control FCM. Expression of Slc8a1, Cacna1c, and Kcnb1 was not different in stimulated and control FCMs. The decrease in APD50 observed after electrical stimulation of FCM in vitro corresponds to the electrophysiological maturation of FCM in vivo. Expression levels of ion channels suggest that some important but not all aspects of the complex process of electrophysiological maturation are promoted by electrical stimulation. Parallel alignment, increased connexin 43 expression, and elongation of FCM are signs of a morphological maturation induced by electrical stimulation.